2019
DOI: 10.1093/jrr/rrz026
|View full text |Cite
|
Sign up to set email alerts
|

Total body irradiation induced mouse small intestine senescence as a late effect

Abstract: Radiation can induce senescence in many organs and tissues; however, it is still unclear how radiation stimulates senescence in mouse small intestine. In this study, we use the bone marrow transplantation mouse model to explore the late effects of total body irradiation on small intestine. Our results showed that almost all of the body hairs of the irradiated mice were white (which is an indication of aging) 10 months after the exposure to radiation. Furthermore, compared with the age-matched control mice, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…As mentioned earlier, many bacterial species and microbiota changes in the skin (Plichta et al, 2017), vagina (Brotman et al, 2014;Bai et al, 2019), oral cavity (Vanhoecke et al, 2015;Zhu et al, 2017;Hou et al, 2018;Anjali et al, 2020;Nishii et al, 2020;Vesty et al, 2020), and GI of humans (Lam et al, 2012; are associated with disease severity and may even be predictive of pathogenesis. Along with the finding that some radiation-induced microbiota changes are persistent out to 6 months (Lam et al, 2012;Zhao et al, 2019;Anjali et al, 2020;Nishii et al, 2020), these data support the use of the microbiota as potentially stable biomarkers for radiation exposure and injury.…”
Section: Microbiome Biomarkers As Biodosimeterssupporting
confidence: 63%
See 1 more Smart Citation
“…As mentioned earlier, many bacterial species and microbiota changes in the skin (Plichta et al, 2017), vagina (Brotman et al, 2014;Bai et al, 2019), oral cavity (Vanhoecke et al, 2015;Zhu et al, 2017;Hou et al, 2018;Anjali et al, 2020;Nishii et al, 2020;Vesty et al, 2020), and GI of humans (Lam et al, 2012; are associated with disease severity and may even be predictive of pathogenesis. Along with the finding that some radiation-induced microbiota changes are persistent out to 6 months (Lam et al, 2012;Zhao et al, 2019;Anjali et al, 2020;Nishii et al, 2020), these data support the use of the microbiota as potentially stable biomarkers for radiation exposure and injury.…”
Section: Microbiome Biomarkers As Biodosimeterssupporting
confidence: 63%
“…However, it has been found that severe postirradiation enteropathy is associated with low mucosal bacterial diversity ( Ferreira et al, 2019 ). In rodent studies, specific findings of microbiota changes in postirradiation fecal samples include increased abundance of the phylum Proteobacteria and family Lactobacillaceae and decreased abundance of families Lachnospiraceae , Ruminococcaceae , and Clostridiaceae , with some changes observed out to 10 months ( Lam et al, 2012 ; Goudarzi et al, 2016 ; Zhao et al, 2019 ; Li et al, 2020 ). In humans, one prospective study of nine gynecologic cancer patients found that Firmicutes and Fusobacterium phyla were significantly decreased in fecal samples pre- versus post-pelvic irradiation ( Nam et al, 2013 ).…”
Section: The Effects Of Radiation On the Microbiomementioning
confidence: 99%
“…After extraction, DNA was treated with DNase-free RNase to remove contaminating RNA. DNA concentration and quality were assessed ( Pandit et al, 2018 ; Zhao et al, 2019 ). Then, the DNA was stored at −20°C for use.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding the molecular mechanism by revealing circRNA–miRNA–mRNA competitive regulatory networks is of great importance. As the recent improvement of RNA-sequencing (RNA-seq) facilitated obtaining huge and accurate results, 8 this technique has become a proper method to detect irradiation-responsive circRNAs in RILI. In a previous study, the lncRNA–miRNA–mRNA network was found to contribute to the RILI process by RNA-seq.…”
Section: Introductionmentioning
confidence: 99%